2022
DOI: 10.1212/nxg.0000000000200015
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Phenotype Associations of Rare Variants in 5 Monogenic Cerebral Small Vessel Disease Genes in 200,000 UK Biobank Participants

Abstract: Background and ObjectivesBased on previous case reports and disease-based cohorts, a minority of patients with cerebral small vessel disease (cSVD) have a monogenic cause, with many also manifesting extracerebral phenotypes. We investigated the frequency, penetrance, and phenotype associations of putative pathogenic variants in cSVD genes in the UK Biobank (UKB), a large population-based study.MethodsWe used a systematic review of previous literature and ClinVar to identify putative pathogenic rare variants in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…In more than 450 000 individuals, we demonstrated that NOTCH3, HTRA1, and COL4A1/2 variants identical to those causing monogenic cSVD are much more frequent than expected in the general population based on the frequency of clinical disease caused by these variants. This is consistent with reports from various population databases, 5,6,36,37 demonstrating that such variants occur in 2 to 3 individuals per 1000. Our results extend previous work by showing association of such variants with disease.…”
Section: Discussionsupporting
confidence: 92%
“…In more than 450 000 individuals, we demonstrated that NOTCH3, HTRA1, and COL4A1/2 variants identical to those causing monogenic cSVD are much more frequent than expected in the general population based on the frequency of clinical disease caused by these variants. This is consistent with reports from various population databases, 5,6,36,37 demonstrating that such variants occur in 2 to 3 individuals per 1000. Our results extend previous work by showing association of such variants with disease.…”
Section: Discussionsupporting
confidence: 92%
“…Earlier work in smaller cohorts (predominantly focused on NOTCH3 ) suggest that pathogenic variants are more frequent than expected based on prevalence of disease phenotype . Some studies identify differences in penetrance, expressivity, and a globally increased risk of stroke and/or vascular dementia . Cho et al reported consistent findings: pathogenic variants in all 3 genes were markedly more frequent than expected based on prevalence of clinical disease phenotypes thought to be caused by these variants.…”
supporting
confidence: 87%
“…The results are balanced between confirmatory vs novel/hypothesis generating. In all 3 genes, the study supports previous data of lower penetrance rates and overestimated variant pathogenicity . A significant proportion of asymptomatic carriers were identified when evaluating for prevalence and incidence of cSVD (median follow-up, 12.6 years).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Despite the reported cases of parkinsonism-related genetic leukoencephalopathy, these cases represent a small percentage of patients with cerebral small vessel disease, with overlapped clinical features and neuroimaging [ 66 , 67 ], indicating the need for genetic testing of patients’ cohorts to confirm its frequency among patients diagnosed currently with VaP. Most cerebral small vessel disease cases are attributed to interaction between environmental factors and multiple genetic variants, while monogenic variants represent a minor percentage (up to 5%) [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%